2017
DOI: 10.1128/cvi.00498-16
|View full text |Cite
|
Sign up to set email alerts
|

Preexisting Immunity, Not Frailty Phenotype, Predicts Influenza Postvaccination Titers among Older Veterans

Abstract: Both preexisting immunity to influenza and age have been shown to be correlates of influenza vaccine responses. Frailty, an indicator of functional impairment in older adults, was also shown in one study to predict lower influenza vaccine responses among nonveterans. In the current study, we aimed to determine the associations between frailty, preexisting immunity, and immune responses to influenza vaccine among older veterans. We studied 117 subjects (age range, 62 to 95 years [median age, 81 years]), divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
(41 reference statements)
6
24
0
Order By: Relevance
“…The results of the present study are in agreement with other recent reports demonstrating a lack of association between frailty and vaccine-induced humoral responses ( 11 , 12 , 14 , 15 ), while differing from some of the earlier studies where frailty was associated with lower seroconversion rates ( 8 10 ). Of note, the recent studies have suggested that the vaccine-induced antibody production is more strongly correlated with pre-existing antibody levels than with frailty stratification ( 14 , 35 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The results of the present study are in agreement with other recent reports demonstrating a lack of association between frailty and vaccine-induced humoral responses ( 11 , 12 , 14 , 15 ), while differing from some of the earlier studies where frailty was associated with lower seroconversion rates ( 8 10 ). Of note, the recent studies have suggested that the vaccine-induced antibody production is more strongly correlated with pre-existing antibody levels than with frailty stratification ( 14 , 35 ).…”
Section: Discussionsupporting
confidence: 85%
“…The results of the present study are in agreement with other recent reports demonstrating a lack of association between frailty and vaccine-induced humoral responses ( 11 , 12 , 14 , 15 ), while differing from some of the earlier studies where frailty was associated with lower seroconversion rates ( 8 10 ). Of note, the recent studies have suggested that the vaccine-induced antibody production is more strongly correlated with pre-existing antibody levels than with frailty stratification ( 14 , 35 ). In this study, both pre-existing HAI titers and post-vaccination seroconversion rates were observed to be similar across frailty groups and a positive correlation between pre-existing and post-vaccination antibody titers was seen similarly to other studies ( 14 , 36 ) confirming that the antibody responses were largely determined by pre-existing antibodies and to a much lesser extent by frailty or age.…”
Section: Discussionsupporting
confidence: 85%
“…A systematic review of high-dose relative to standard-dose influenza vaccine trials, showed that the better antibody responses to high-dose influenza vaccine was independent of sex, age > 75 years old, frailty, and chronic conditions [52]. This is supported by individual studies from Singapore [53], Germany [49], and the U.S. [54], all of which reported that frailty did not have a significant effect on antibody titres following standard dose vaccination in adults 60 and over. Another study originating from the U.S. found the opposite, where antibody responses were significantly impaired in adults that were frail [55].…”
Section: Impact Of Frailty On Outcomes Of Influenzamentioning
confidence: 94%
“…11 The other found no difference in post-vaccination geometric mean titer ratios between frail and non-frail groups of veterans aged 62 years (mean age D 81 years). 12 To our knowledge, similar studies of adults younger than 65 years of age have not been conducted. The purpose of this study was to examine the effect of physical frailty on immune response to influenza vaccine in community-dwelling adults 50 years of age and determine if those responses differed by age.…”
Section: Introductionmentioning
confidence: 93%